Building health throughout the life course : concepts, implications, and application in public health - Vega, Enrique; Hommes, Carolina; Ambrose, Ashley (Pan American Health Organization, 2021)
Building Health Throughout the Life Course elucidates how health develops and changes throughout the life course, and how the use of the life course approach among public health practitioners can ensure that health as a human right is achieved for all individuals. It describes the life course vision of health that focuses not only on diseases and their consequences, but rather on achieving long, healthy, active, and productive lives. This book aims to help decision-makers and public health professionals to understand the life course meaning and concepts, which is essential to comprehend how health develops and changes throughout the life course. The book also describes how the life course model allows us to address health disparities by generating mechanisms to improve health and well-being by promoting the vision of health as the product of a series of experiences that contribute to or detract from health in the near and long term.